Inkubatory technologiczne jako narzędzie polepszania konkurencyjności gospodarki polskiej - Galewski, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The article describes the idea of incubators of technology and shows examples of implementation of this concept in Poland and on the foreign markets. Some of the companies described were successful, but some of them did not manage to compete on the market. The author points out the actions that should be taken to help the companies to leave incubators successfully. The article emphasises also the importance of supporting the development of the new technologies for enhancing the competitiveness of the Polish economy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 97-110